Examining Dark Triad traits in relation to well-being and cognitive-emotional regulation strategies - Gómez-Leal, Raquel; Gutiérrez-Cobo, María José; Megías-Robles, Alberto; Fernández-Berrocal, Pablo (My University, 2023)
The Dark Triad (DT) construct -Machiavellianism, narcissism, and psychopathy- has usually been correlated with maladaptive strategies of emotion regulation. These strategies have shown a negative relationship with the components of well-being: affective well-being (AWB), and cognitive well-being (CWB). The aim of this study was to analyze the relationship between DT traits and the emotional regulation strategies (adaptive and maladaptive strategies) and its influence in well-being. For this objective, 678 participants (Mage= 35.03; 53.1% women) were assessed in these variables through the Short Dark Triad (SD-3), the Cognitive Emotional Regulation Questionnaire (CERQ-36), the Positive and Negative Affect Schedule (PANAS), and Satisfaction with Life Scale (SWB). Our findings revelated that Machiavellianism was indirectly and negatively associated to CWB through the effect of maladaptive strategies and AWB, and indirectly and positively related to CWB through the effect of adaptive strategies and AWB. Narcissism was indirectly positively related to CWB through the effect of adaptive strategies and AWB. Finally, psychopathy was indirectly negatively related to CWB through the effect of adaptive strategies and AWB. These findings may be a good tool for the development and implementation of better prevention and treatment programs aimed at decreasing the negative consequences suffered by individuals with high DT scores.
Keywords: Psicopatología - Congresos; Dark triad; Machiavellianism; Psychopathy; Narcissism; Well-being; Emotion regulation strategies